Influence of the laser ablation surface pre-treatment over the ageing resistance of metallic adhesively bonded joints. (March 2021) - Moroni, F.; Musiari, F.; Favi, C.
Abstract: In order to prevent the generation of a potential weakness at the substrate/adhesive interface of adhesively bonded joints, many methods were developed during the decades to pre-treat the substrates surfaces before the deposition of the adhesive. Experimental tests were carried out to simulate the real environmental conditions in which the joints have to work characterizing the mechanical properties of the joints caused by the exposition to high temperature, moisture, presence of chemical agents. The industrial need towards long-scale problem lead to the development of specific accelerated ageing methods able to induce in few weeks the same damage mechanisms within the joints which arise in years during their working life. In this work, different surface laser pre-treatments were studied with a focus on the influence that pre-treatments produce over the variation of the tensile failure load of Single Lap Joints (SLJ), previously subjected to different accelerated ageing cycles. Simple degreasing and grit blasting were also considered as reference treatments. The materials chosen for the manufacturing of the substrates were an aluminium alloy (AA 6082-T6) and a stainless steel (AISI 304). Three different accelerated ageing techniques were tested and compared to each other: (i) a cycle involving the simultaneous presence of high temperature gradient and moisture (method A), (ii) the immersion into an alkaline foam-forming cleanser (method B), and (iii) the immersion into an acid foam-forming cleanser (method C). The results showed that, while the method A did not significantly modify the mechanical strength of the joints, the method B and C resulted detrimental for the mechanical performance of the joints, even if their sensitivity to the tested pre-treatments was different. In particular, for both aluminum and stainless steel joints, it was noticed that the laser pre-treatment was able to reduce the loss of strength produced by the ageing process in comparison with the two reference pre-treatments. However, this result was also dependent of the specific value of energy density used for the laser ablation during the joints pre-treatment.